Traduire la poétique de l’ambiguïté de Los adioses de Juan Carlos Onetti ? - Marta Álvarez Izquierdo (Itinéraires, 2019)
The work of Juan Carlos Onetti is characterized by his conception of literature, which, as he has argued, is in need of an urgent renovation. The aim of this renovation is to represent more adequately the twentieth-century society and the people living in it. This article offers a study of the novel Los adioses, written by Juan Carlos Onetti. Its main objective is to analyze different narratological methods employed by Onetti and to offer a better understanding of the “poetic of ambiguity” upon which is based the invention of a new aesthetic. Can imaginaries be translated and how? Does the French reader have access to the same literary universe as the Spanish reader? Our aim is to look at the Spanish original and its French translation from a comparative perspective. By doing so, we propose a study of the duplicity of the narrative, the function of the gaze in writing, and the eventual deconstruction of the narrative.